2022
DOI: 10.3390/toxins14070453
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Field-Evolved Resistance to Afidopyropen, a Novel Insecticidal Toxin Developed from Microbial Secondary Metabolites, in Bemisia tabaci

Abstract: Afidopyropen, a newly identified chemical, is a derivative of pyripyropene A, which is produced by the filamentous fungus Penicillium coprobium. It is a promising novel pesticide applied against whiteflies in agriculture. In this study, the reversion and selection, cross-resistance patterns, synergistic effects, and fitness costs of afidopyropen resistance were studied in a field-developed resistant population of B. tabaci. Compared to a reference MED-S strain, the field-developed resistant Haidian (HD) popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Resistance selection experiments showed that resistance to afidopyropen in one strain was stably increased from the second to the sixth generation. Additionally, this resistance was subsequently stabilized between the seventh and tenth generations [ 43 ]. Thus, in contrast to abamectin, B. tabaci is expected to rapidly develop resistance to afidopyropen when exposed to this insecticide within several generations.…”
Section: B Tabaci Resistance To Pesticides Of Different Classesmentioning
confidence: 99%
See 4 more Smart Citations
“…Resistance selection experiments showed that resistance to afidopyropen in one strain was stably increased from the second to the sixth generation. Additionally, this resistance was subsequently stabilized between the seventh and tenth generations [ 43 ]. Thus, in contrast to abamectin, B. tabaci is expected to rapidly develop resistance to afidopyropen when exposed to this insecticide within several generations.…”
Section: B Tabaci Resistance To Pesticides Of Different Classesmentioning
confidence: 99%
“…In an abamectin-resistant MEAM1 (B) strain, the oxidase inhibitor piperonyl butoxide (PBO) and the GST inhibitor diethyl maleate (DEM) produce significant synergistic effects on abamectin, indicating that enhanced metabolism mediated by P450 monooxygenase and GST activity, but not esterase activity, may be involved in abamectin resistance [ 40 ]. In an afidopyropen-resistant strain, PBO also showed significant synergism with afidopyropen, suggesting that oxidative metabolism may be one mechanism that results in afidopyropen resistance [ 43 ].…”
Section: B Tabaci Resistance To Pesticides Of Different Classesmentioning
confidence: 99%
See 3 more Smart Citations